Hubungan Antara Tingkat Religiusitas Dengan Tingkat Stres Pada Lansia Di Panti Wredha Dharma Bhakti Surakarta - Swasono, Muhammad Agung; , Prof. Dr. Mohammad Fanani, dr. Sp. Kj (K); , Dr. Erna Herawati, Sp.K.J (2015)
Background: The changes in physical, mental and social can be a source of stress for the elderly. From previous studies, the resistance to stress is highly correlated with the level of faith and religiousity. In elder age, a person tend to have more religious life and it increase in quantity as the person gets older. Purpose: To acknowledge the correlation between the level of religiousity and the level of stress in the elderly in Panti Wredha Dharma Bhakti Surakarta. Methods: This study used analytic observational cross-sectional approach and to examine the correlation between the two variables, the method used Pearson's correlation test. The study involved 40 respondents who became residents of Panti Wredha Dharma Bhakti Surakarta with the age of respondent were above 60 years old, agreed to volunteer and adherence of Muslims. Sampling was taken by using total sampling technique. Results: The research analysis found r = -0,797 and p < 0.001 were very significant in statistic. Conclusion: There is correlation between the level of religiousity and the level of stress in the elderly in Panti Wredha Dharma Bhakti Surakarta.